2021
DOI: 10.1002/jor.25050
|View full text |Cite
|
Sign up to set email alerts
|

Painful temporomandibular joint overloading induces structural remodeling in the pericellular matrix of that joint's chondrocytes

Abstract: Mechanical stress to the temporomandibular joint (TMJ) is an important factor in cartilage degeneration, with both clinical and preclinical studies suggesting that repeated TMJ overloading could contribute to pain, inflammation, and/or structural damage in the joint. However, the relationship between pain severity and early signs of cartilage matrix microstructural dysregulation is not understood, limiting the advancement of diagnoses and treatments for temporomandibular joint‐osteoarthritis (TMJ‐OA). Changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
(120 reference statements)
0
6
0
Order By: Relevance
“…Detailed investigations of the pericellular matrix surrounding chondrocytes within the TMJ cartilage following loading showed that collagen VI increased in both the 2 N and 3.5 N groups, whereas there was a greater increase in aggrecan non-epitopes in the 3.5 N group. These results suggest that aggrecan fragmentation may be relevant to pain responses and the severity of structural damage to the TMJ ( 126 ).…”
Section: Preclinical Studies For Tmjoa and Pain From Tmjmentioning
confidence: 96%
“…Detailed investigations of the pericellular matrix surrounding chondrocytes within the TMJ cartilage following loading showed that collagen VI increased in both the 2 N and 3.5 N groups, whereas there was a greater increase in aggrecan non-epitopes in the 3.5 N group. These results suggest that aggrecan fragmentation may be relevant to pain responses and the severity of structural damage to the TMJ ( 126 ).…”
Section: Preclinical Studies For Tmjoa and Pain From Tmjmentioning
confidence: 96%
“…Eventually, buckling during normal valve opening initiates tears that propagate and cause valve failure. 21 Our lab has synthesized and characterized a family of synthetic proteoglycan analogs, [22][23][24][25][26][27][28] termed biomimetic proteoglycans (BPGs).…”
Section: Introductionmentioning
confidence: 99%
“…Our lab has synthesized and characterized a family of synthetic proteoglycan analogs, 22–28 termed biomimetic proteoglycans (BPGs). BPGs have a linear poly(acrylic acid) (PAA) backbone whose length can be tuned, enabling synthesis of BPGs of varying size.…”
Section: Introductionmentioning
confidence: 99%
“…19,22,45 Animal studies showed that activated osteoclasts may also induce sensory innervation and pain in OA. 13,37,45 Thus, interventions that reduce subchondral bone remodeling may be beneficial to protect against cartilage degradation and attenuate OA pain. 19 Many clinicians prescribe nonpharmacologic methods, such as exercise and walking, for patients with OA as first-line treatment according to the 2019 guidelines of…”
mentioning
confidence: 99%
“…19,22,45 Animal studies showed that activated osteoclasts may also induce sensory innervation and pain in OA. 13,37,45 Thus, interventions that reduce subchondral bone remodeling may be beneficial to protect against cartilage degradation and attenuate OA pain. 19…”
mentioning
confidence: 99%